Effective Host-Directed Therapy for Tuberculosis by Depletion of Myeloid-Derived Suppressor Cells and Related Cells Using a Diphtheria Toxin Fusion Protein. (6th May 2021) - Parveen, Sadiya; Lun, Shichun; Urbanowski, Michael E; Cardin, Mitchell; Shen, Jessica; Murphy, John R; Bishai, William R
Abstract: Myeloid-derived suppressor cells (MDSCs) are present in elevated numbers in tuberculosis patients and have been found to be permissive for Mycobacterium tuberculosis proliferation. To determine whether depletion of MDSCs may improve host control of tuberculosis, we used a novel diphtheria toxin-based fusion protein DABIL-4 that targets and depletes interleukin 4 (IL-4) receptor-positive cells. We show that DABIL-4 depletes both polymorphonuclear MDSCs and monocytic MDSCs, increases interferon-γ  + T cells, and reduces the lung bacillary burden in a mouse tuberculosis model. These results indicate that MDSC-depleting therapies targeting the IL-4 receptor are beneficial in tuberculosis and offer an avenue towards host-directed tuberculosis therapy. Abstract : Our study demonstrates that the diphtheria fusion toxin protein DABIL-4 depletes immunosuppressive cell populations, including MDSCs and M2 macrophages, thereby potentiating the recruitment and cytotoxic functions of the effector T cells resulting in better clearance of Mycobacterium tuberculosis in murine lungs.